The Correlation Between Students’ Remarkable Experiences and Their Ability in Recount Text Writing - Eka Rindi Astuti (International Conference on Education and Language (ICEL), 2014)
Junior high school students got many difficulties in recount text writing. They were difficult to tell past events or their experience in a good writing. Numbers of their experiences might support their recount-text writing. This research aimed to study if the numbers of the students’ experiences are correlated to their writing achievement. Because the term ‘experience’ has a very general concept, the writer limited it into remarkable experiences. An experience turns to be a remarkable one if it gets a significance of notice and attention from the sensor. This research was conducted to one group, which represented the grade-eight students of SMPN 20 Bandar Lampung. The group was selected with Cluster Sampling Technique. Data were collected with a questionnaire and writing test. Then, they were analyzed with r-Product Moment. Based on the computation, rxy: 0,618 was greater than the r-table in 1%: 0,449 and 5%: 0,349. Therefore, the alternative hypothesis (Ha) was accepted, while the null hypothesis (Ho) was rejected. The writer concluded that there was a correlation between students’ remarkable experience and their ability in writing recount text.